FORMULASI GRANUL EFFERVESCENT SARI BUAH JAMBU METE (Annacardium ocidentale L.) (PHARMACON, 2017)
FORMULASI GRANUL EFFERVESCENT SARI BUAH JAMBU METE (Annacardium ocidentale L.) Lucia Santosa1), Paulina V. Y. Yamlean1), Hamidah Sri Supriati1)1)Program Studi Farmasi FMIPA UNSRAT, 95115 ABSTRACT            Cashew fruit can be regarded as a fruit that contain high of vitamin C. Every 100g of cashew fruit contains vitamin C as much as 197mg. Vitamin C was needed to increase the endurance. The aims of this study was to make an effervescent granule preparation of juice of cashew and to know the effect of concentration differences of acid and base on the physical properties of effervescent granule. The effervescent granules of cashew juice are prepared in four formulations with variations of the ratio of Sodium Bicarbonate and acids (tartaric acid and citric acid) as follows: formula 1 = 2: (2: 1), formula 2 = 2.5: (2: 1) , Formula 3 = 3: (1: 2), formula 4 = 3: (2: 2). In formula 1, the test results obtained was 0.8% moisture content, flow rate 9.7 seconds, angle of repost 17.60o and dispersion time 1.28 minutes. In formula 2, the test results obtained that the water content test of 0.9%, the flow rate of  7.6 seconds, the angle of repost of 17.62o and the dispersion time of 1.38 minutes. In formula 3, the test results obtained that the water content test of 0.4%, the flow rate of 5.5 seconds, the angle of repost of 19.33o and the dispersion time of 1.50 minutes. In the formula 4, the test results obtained was 0.5% moisture content, 5.4 seconds flow velocity, the angle of repost of 18.28o and the dispersion time of 1.52 minutes. Keywords: Cashew fruit (Annacardium ocidentale L.), Effervescent Granule ABSTRAKJambu Mete dapat dikatakan sebagai buah yang memiliki vitamin C tinggi. Setiap 100g Jambu Mete mengandung vitamin C sebanyak 197mg. Vitamin C sangat diperlukan untuk meningkatkan daya tahan tubuh. Penelitian ini bertujuan untuk membuat formulasi sediaan granul effervescent sari buah Jambu Mete dan untuk mengetahui pengaruh perbedaan konsentrasi asam dan basa  terhadap sifat fisik granul effervescent. Granul effervescent sari buah Jambu Mete dibuat dalam empat formulasi dengan variasi rasio Natrium Bikarbonat dan asam (asam tartrat dan asam sitrat) sebagai berikut : formula 1 = 2 : (2 : 1), formula 2 = 2,5 : (2 : 1), formula 3 = 3 : (1 : 2), formula 4 = 3 : (2 : 2). Pada formula 1, didapatkan hasil pengujian kadar air 0,8%, kecepatan alir  9,7 detik, sudut diam 17,60o dan waktu dispersi 1,28 menit. Pada formula 2, didapatkan hasil pengujian kadar air 0,9%, kecepatan alir 7,6 detik, sudut diam 17,62o dan waktu dispersi 1,38 menit. Pada formula 3, didapatkan hasil pengujian kadar air 0,4%, kecepatan alir 5,5 detik, sudut diam 19,33o dan waktu dispersi 1,50 menit. Pada formula 4, didapatkan hasil pengujian kadar air 0,5%, kecepatan alir 5,4 detik, sudut diam 18,28o dan waktu dispersi 1,52 menit. Kata Kunci : Jambu Mete (Annacardium ocidentale L.), Granul Effervescent